Graphene separation membrane with wrinkle structure and preparation method thereof
By introducing a wrinkle structure into the graphene separation membrane, the problem of low porosity of the existing graphene separation membrane is solved, the porosity and water flux of the membrane are improved, and efficient water treatment and photothermal conversion effects are achieved.
Patent Information
- Application Number
- CN202411772984.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The porosity of the existing graphene separation membrane is low, resulting in its permeability flux far below the theoretical value, making it difficult to meet the needs of efficient water treatment.
By using strong tape to form a wrinkle structure in the graphene separation layer, the number of pores per unit membrane area is increased, thereby increasing the porosity of the membrane. At the same time, graphene with a wrinkled structure has good photothermal conversion ability, and can heat water on the surface of the film under sunlight, reduce its viscosity, and thus increase water flux.
The porosity and water flux of the graphene separation membrane are improved, its separation performance is enhanced, it can effectively remove pollutants in water, and has good photothermal conversion performance.
Smart Images

Figure CN119680401A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a graphene separation membrane with a pleated structure and a preparation method thereof. Background Art
[0002] Water pollution is a serious environmental challenge facing the world today. It stems from various industrial emissions, agricultural activities, domestic sewage and inappropriate waste disposal methods, resulting in excessive levels of harmful substances in water bodies, which seriously threatens the balance of the ecosystem and the sustainable use of water resources, and even human health. Membrane separation water treatment technology is an efficient and advanced wastewater treatment technology that uses membranes with different pore sizes to selectively separate and enrich suspended matter, organic matter, heavy metal ions and other substances in water. This technology has the advantages of high separation efficiency, low energy consumption and simple operation, and has been widely used in the field of water treatment. Through membrane separation technology, pollutants in water can be effectively removed, water quality can be improved, and water resources can be reused. At the same time, this technology also has the characteristics of small footprint and simple equipment maintenance, which has brought revolutionary changes to the water treatment industry.
[0003] Traditional separation membranes usually have a contradiction between permeability and selectivity, that is, increasing the permeability of the membrane often reduces the selectivity of the membrane, and vice versa. Graphene separation membrane is a thin film made of graphene material, which can efficiently separate harmful substances in water, such as heavy metal ions and organic pollutants. It has excellent properties such as high flux, high selectivity and high stability, and shows great application potential in the field of water treatment. At present, the most common graphene separation membrane is made by orderly stacking graphene nanosheets and has a layered structure. However, the porosity of this type of graphene separation membrane is very low, resulting in its permeation flux far less than the theoretical value. Therefore, it is of great value and significance to prepare a graphene separation membrane with high porosity and ultra-high flux. Summary of the invention
[0004] In view of the problem that the porosity of existing graphene separation membranes is low and their permeation flux is far less than the theoretical value, the purpose of the present invention is to provide a graphene separation membrane with a pleated structure and a preparation method thereof. The basic concept of the present invention is to use a strong adhesive tape to form a pleated structure on the graphene separation layer, increase the number of pores per unit membrane area, that is, increase the membrane porosity; the pleated graphene has good photothermal conversion ability, can heat the water on the membrane surface under sunlight, significantly reduce the viscosity of water, and thus further improve its water flux.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing a graphene separation membrane with a wrinkled structure, comprising the following steps: firstly preparing a nanofiber dispersion liquid and a graphene dispersion liquid respectively, depositing a nanofiber layer on a porous membrane substrate, then depositing a graphene layer on the nanofiber layer, then turning over the obtained material and making the graphene layer closely adhere to a pre-stretched elastic tape, tearing off the porous membrane substrate, releasing the elastic tape to shrink the nanofiber layer and the graphene layer, then coating a layer of organic polymer casting liquid on the shrunk nanofiber layer, immersing it in anhydrous ethanol for phase conversion, and finally peeling off the prepared membrane from the elastic tape to obtain the membrane.
[0007] Based on the above technical solution, further, the porous membrane substrate is a polyacrylonitrile membrane, polyvinylidene fluoride membrane, mixed cellulose ester membrane, polypropylene membrane, polycarbonate membrane, polytetrafluoroethylene membrane, polyethersulfone membrane, polysulfone membrane with a flat structure, and its pore size range is 0.01 to 10.0 μm.
[0008] Based on the above technical solution, further, the graphene includes graphene obtained by chemical exfoliation of graphite and its derivatives, which are one or a mixture of two or more of graphene oxide, reduced graphene oxide, hydroxylated graphene, carboxylated graphene, amino graphene or sulfonated graphene.
[0009] Based on the above technical solution, further, the nanofibers are carbon material nanofibers, metal nanofibers, metal oxide nanofibers, organic polymer nanofibers or inorganic nitrogen / carbide nanofibers.
[0010] Based on the above technical solution, further, the carbon material nanofiber is a mixture of one or two of carbon nanotubes or carbon nanofibers; the metal nanofiber is a mixture of one or more of gold nanofibers, silver nanofibers, copper nanofibers, cobalt nanofibers, iron nanofibers, and nickel nanofibers; the metal oxide nanofiber is a mixture of one or more of iron oxide nanofibers, zinc oxide nanofibers, titanium oxide nanofibers, aluminum oxide nanofibers, gallium oxide nanofibers, or tin oxide nanofibers; the organic polymer nanofiber is a mixture of one or two of poly(p-phenylene terephthalamide) nanofibers or poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid); the inorganic nitrogen / carbide nanofiber is a mixture of one or two of silicon carbide nanofibers and boron nitride nanofibers.
[0011] Based on the above technical solution, further, the deposition method is one of vacuum filtration, spraying, and evaporation self-assembly.
[0012] Based on the above technical solution, further, the elastic tape is pre-stretched to 150% to 400% of its original length.
[0013] Based on the above technical solution, further, the organic polymer casting solution is a viscous solution obtained by uniformly stirring a high molecular organic polymer, a pore-forming agent and an organic solvent at 40 to 80°C.
[0014] Based on the above technical solution, further, the high molecular polymer is a mixture of one or more of polyacrylonitrile, polyvinylidene fluoride, polyether sulfone, and polysulfone; the pore-forming agent is a mixture of one or more of polyvinyl pyrrolidone and polyethylene glycol; and the organic solvent is a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0015] Based on the above technical solution, further, the mass ratio of the high molecular polymer, the pore-forming agent and the organic solvent is 1:(0.2-1):5-10.
[0016] In a second aspect, the present invention provides a graphene separation membrane with a wrinkled structure obtained by the above preparation method.
[0017] Based on the above technical solution, further, the graphene separation membrane has a layered structure, including a porous organic polymer base layer, a nanofiber middle layer and a wrinkled graphene surface layer.
[0018] Based on the above technical solution, further, the thickness of the porous organic polymer substrate layer is 20 to 200 μm, the thickness of the nanofiber middle layer is 1 to 50 μm, and the thickness of the wrinkled graphene surface layer is 1 to 50 μm.
[0019] In a third aspect, the present invention provides application of the above-mentioned graphene separation membrane with a wrinkled structure in wastewater treatment.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The graphene separation membrane with a pleated structure prepared by the present invention has high porosity, excellent separation performance, and can effectively convert sunlight into thermal energy, heat water on the surface of the membrane, reduce its viscosity, and further improve its own water permeability. The preparation method of the graphene separation membrane with a pleated structure is simple, does not require expensive chemical reagents and special equipment, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0023] Figure 1 This is a low-magnification scanning electron microscope image of the surface of the wrinkled graphene oxide separation membrane prepared in Example 1;
[0024] Figure 2 This is a high-magnification scanning electron microscope image of the surface of the wrinkled graphene oxide separation membrane prepared in Example 1;
[0025] Figure 3 is a scanning electron microscope image of a cross section of the wrinkled graphene separation membrane prepared in Example 2;
[0026] Figure 4 The wrinkled graphene separation membrane prepared in Example 3 was heated to 645 W m -2 The photothermal conversion performance results under sunlight.
[0027] Figure 5 This is a graph showing the pure water permeation rate results of the wrinkled graphene separation membrane prepared in Example 3 before and after sunlight irradiation. DETAILED DESCRIPTION
[0028] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0029] Example 1
[0030] (1) Synthesis of graphene oxide: Weigh 1.0g natural graphite powder and 0.5g sodium nitrate and add them to 25mL concentrated sulfuric acid, and stir magnetically for 8h. Then, slowly add 3.0g potassium permanganate in an ice bath and continue stirring for 4h. Subsequently, raise the temperature to 35°C, stir for 2h, then slowly add 46mL deionized water, and then stir for 0.5h and add 140mL deionized water. After that, quickly add 10mL 30% hydrogen peroxide solution. The product is freeze-dried after multiple centrifugation and water washing;
[0031] (2) Preparation of graphene oxide dispersion: 50 mg of graphene oxide solid was weighed and added into 1 L of deionized water, stirred for 1 h, and then ultrasonically treated in an ultrasonic cleaner for 1 h;
[0032] (3) Preparation of carbon nanotube dispersion: 200 mg of commercially available single-walled carbon nanotube powder and 500 mg of sodium dodecyl sulfate were weighed and added to 400 mL of deionized water, and then stirred with a magnetic stirrer for 30 min and ultrasonicated with an ultrasonic cell disruptor for 1 h (ultrasound on for 3 s / off for 5 s) for 3 to 5 cycles. The obtained carbon nanotube dispersion was centrifuged at 8000 rpm for 10 min, and the supernatant was placed in a beaker.
[0033] (4) taking a mixed cellulose ester membrane with a pore size of 0.22 μm and placing it in a vacuum filtration device, filtering 2 mL of the carbon nanotube dispersion prepared in step (3), and then filtering 2 mL of the graphene oxide dispersion prepared in step (2), and drying the obtained material at a temperature not exceeding 80° C.;
[0034] (5) stretching the 3M VHB elastic adhesive by 300% in all directions, and then closely attaching the side of the mixed cellulose ester film having graphene oxide obtained in step (4) to the elastic adhesive, and then slowly tearing off the mixed cellulose ester film and releasing the elastic tape to obtain a wrinkled graphene oxide / carbon nanotube layer;
[0035] (6) Add 5.0 g of polyethersulfone powder and 2.5 g of polyvinyl pyrrolidone powder to 25.0 g of N-methylpyrrolidone, stir at 60° C. for 4 h to obtain a casting solution, drop the casting solution onto the wrinkled graphene oxide obtained in step (5), and spin coat it at 1000 rpm for 20 s; then, quickly immerse it in anhydrous ethanol for phase inversion, and after 30 min, peel off the obtained membrane from the elastic glue to obtain a graphene separation membrane with a wrinkled structure.
[0036] Figure 1 This is a low-magnification scanning electron microscope image of the surface of the prepared graphene oxide separation membrane. It can be seen that there are no defects such as cracks and holes on the membrane surface.
[0037] Figure 2 This is a high-magnification scanning electron microscope image of the surface of the prepared graphene oxide separation membrane, in which the typical wrinkled structure can be seen.
[0038] The thickness of the graphene oxide / carbon nanotube layer of the prepared wrinkled graphene oxide separation membrane is 10 μm, and the thickness of the underlying porous polyethersulfone substrate is 55 μm.
[0039] The pure water permeation rate of the wrinkled graphene oxide separation membrane was 45 L m -2 h -1 bar -1 The retention rate of molecules such as methyl blue and Congo red is >99%, showing good separation performance.
[0040] Example 2
[0041] (1) Synthesis of graphene oxide: Weigh 1.0g natural graphite powder and 0.5g sodium nitrate and add them to 25mL concentrated sulfuric acid, and stir magnetically for 8h. Then, slowly add 3.0g potassium permanganate in an ice bath and continue stirring for 4h. Subsequently, raise the temperature to 35°C, stir for 2h, then slowly add 46mL deionized water, and then stir for 0.5h and add 140mL deionized water. After that, quickly add 10mL 30% hydrogen peroxide solution. The product is freeze-dried after multiple centrifugation and water washing;
[0042] (2) Preparation of graphene dispersion: 50 mg of graphene oxide solid was weighed and added into 1 L of deionized water, stirred for 1 h, and then ultrasonically treated in an ultrasonic cleaner for 1 h; 80 mL of the dispersion was measured and poured into a 100 mL polytetrafluoroethylene reactor, and reduced at 120 °C for 6 h;
[0043] (3) Preparation of carbon nanotube dispersion: Weigh 200 mg of commercially purchased multi-walled carbon nanotube powder and 500 mg of sodium dodecyl sulfate and add them to 400 mL of deionized water, then stir with a magnetic stirrer for 30 min and ultrasonic cell disruptor for 1 h (ultrasound on 3 s / off 5 s) alternately for 3 to 5 cycles. Centrifuge the obtained carbon nanotube dispersion at 8000 rpm for 10 min, and take the supernatant and place it in a beaker;
[0044] (4) Place a polyvinylidene fluoride membrane with a pore size of 0.1 μm in a vacuum filtration device, filter 2 mL of the carbon nanotube dispersion prepared in step (3), and then filter 2 mL of the graphene dispersion prepared in step (2). The obtained sample is dried at a temperature not exceeding 80° C.;
[0045] (5) stretching the 3M VHB elastic adhesive by 300% in all directions, and then closely attaching the graphene side of the polyvinylidene fluoride film prepared in step (4) to the elastic adhesive, and then slowly tearing off the polyvinylidene fluoride film and releasing the elastic tape to obtain a wrinkled graphene / carbon nanotube layer;
[0046] (6) Add 5.0 g of polyvinylidene fluoride powder and 5.0 g of polyvinyl pyrrolidone powder to 25.0 g of N-methylpyrrolidone, stir at 60° C. for 4 h to obtain a casting solution, drop the casting solution onto the wrinkled graphene obtained in step (5), and spin coat it at a rotation speed of 1000 rpm for 20 s; then, quickly immerse it in anhydrous ethanol for phase inversion, and after 30 min, peel off the obtained membrane from the elastic glue to obtain a graphene separation membrane with a wrinkled structure.
[0047] Figure 3 The scanning electron microscope image of the cross-section of the prepared graphene separation membrane shows a typical layered structure. The upper layer is a wrinkled graphene / carbon nanotube layer with a thickness of about 12μm, and the lower layer is a porous polyvinylidene fluoride substrate with a thickness of 75μm.
[0048] Example 3
[0049] (1) Synthesis of graphene oxide: Weigh 1.0g natural graphite powder and 0.5g sodium nitrate and add them to 25mL concentrated sulfuric acid. Stir magnetically for 8h. Then, slowly add 3.0g potassium permanganate in an ice bath and continue stirring for 4h. Then, raise the temperature to 35°C, stir for 2h, slowly add 46mL deionized water, and then stir for 0.5h and add 140mL deionized water. Then, quickly add 10mL 30% hydrogen peroxide solution. The product is centrifuged and washed with water several times, then freeze-dried;
[0050] (2) Preparation of graphene dispersion: 10 mg of graphene oxide solid was weighed and added to 200 mL of deionized water. After stirring for 1 h, the mixture was ultrasonically treated in an ultrasonic cleaner for 1 h. Then, 5 μL of hydrazine hydrate solution and 140 μL of ammonia water were added and reduced at 60° C. for 10 min to obtain a graphene dispersion.
[0051] (3) Preparation of carbon nanotube dispersion: Weigh 200 mg of single-walled carbon nanotube powder and 500 mg of sodium dodecyl sulfate and add them to 400 mL of deionized water, then stir with a magnetic stirrer for 30 min and ultrasonic cell disruptor for 1 h (ultrasound on 3 s / off 5 s) alternately for 3 to 5 cycles. Centrifuge the obtained carbon nanotube dispersion at 8000 rpm for 10 min, and take the supernatant and place it in a beaker;
[0052] (4) Take a polyacrylonitrile membrane with a pore size of 0.22 μm and install it in a vacuum filtration device, filter 2 mL of the carbon nanotube dispersion prepared in step (3), and then filter 2 mL of the graphene dispersion prepared in step (2), and dry the obtained sample at a temperature not exceeding 80° C.;
[0053] (5) stretching the 3M VHB elastic adhesive by 400% in all directions, and then closely attaching the graphene side of the polyacrylonitrile film prepared in step (4) to the elastic adhesive, and then slowly tearing off the polyacrylonitrile film and releasing the elastic tape to obtain a wrinkled graphene / carbon nanotube layer;
[0054] (6) Add 5.0 g of polyethersulfone powder and 2.5 g of polyvinylpyrrolidone powder to 25.0 g of N,N-dimethylformamide, and stir at 60°C for 4 h to obtain a casting solution; drop the casting solution onto the wrinkled graphene obtained in step (5), and spin coat it at a speed of 1000 rpm for 30 s; then, quickly immerse it in anhydrous ethanol for phase inversion, and after 30 min, peel off the obtained membrane from the elastic glue to obtain a graphene separation membrane with a wrinkled structure.
[0055] The thickness of the graphene / carbon nanotube layer of the prepared wrinkled graphene separation membrane is 25 μm, and the thickness of the porous polyethersulfone substrate is 72 μm.
[0056] Figure 4 The wrinkled graphene separation membrane was prepared under a light intensity of 645 W m -2 The relationship between the surface temperature and the exposure time under sunlight. As can be seen from the figure, the surface temperature of the wrinkled graphene film increased from room temperature 22.4℃ to 52.4℃ within 1 minute, showing excellent light-to-heat conversion ability.
[0057] Figure 5 The pure water permeation rate of the wrinkled graphene membrane before and after sunlight irradiation is 36.5 L m -2 h -1 bar -1 , significantly increased to 68.4 L m -2 h -1 bar -1 , the pure water penetration rate is improved significantly.
[0058] Example 4
[0059] (1) Synthesis of graphene oxide: Weigh 1.0g natural graphite powder and 0.5g sodium nitrate and add them to 25mL concentrated sulfuric acid. Stir magnetically for 8h. Then, slowly add 3.0g potassium permanganate in an ice bath and continue stirring for 4h. Then, raise the temperature to 35°C, stir for 2h, slowly add 46mL deionized water, stir for 0.5h, add 140mL deionized water, and then quickly add 10mL 30% hydrogen peroxide solution. The product was centrifuged and washed with water several times, and then freeze-dried;
[0060] (2) Preparation of sulfonated graphene dispersion: The concentration was 100 mg L -1 200 mL of graphene oxide dispersion was adjusted to pH 9-10 with 5 wt% sodium carbonate solution, and then 600 mg of sodium borohydride was added. The mixture was reacted at 80 ° C with stirring for 1 h. The resulting precipitate was separated by centrifugation, washed with water several times, and then redispersed in water using ultrasound. 46 mg of p-aminobenzenesulfonic acid and 18 mg of sodium nitrite were weighed and added to an ice-cooled HCl solution to obtain an aryl diazonium salt; the diazonium salt solution was then added to the above-mentioned partially reduced graphene oxide dispersion and reacted for 2 h under ice bath conditions; the obtained product was separated by centrifugation, washed several times, and then redispersed in water. After adding 5 μL of hydrazine hydrate, the mixture was reacted at 100 ° C for 12 h to obtain a sulfonated graphene dispersion.
[0061] (3) Preparation of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) dispersion: 10 mL of commercially purchased poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) dispersion with a concentration of 1 wt% was measured and diluted to 100 mL with deionized water;
[0062] (4) taking a polycarbonate membrane with a pore size of 0.1 μm and placing it in a vacuum filtration device, filtering 1 mL of the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) dispersion prepared in step (3), and then filtering 2 mL of the sulfonated graphene dispersion prepared in step (2), and drying the obtained sample at a temperature not exceeding 80° C.;
[0063] (5) stretching the 3M VHB elastic adhesive by 300% in all directions, and then closely attaching the polycarbonate film obtained in step (4) with the sulfonated graphene on the elastic adhesive, and then slowly tearing off the polycarbonate film and releasing the elastic tape to obtain a wrinkled graphene / poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) layer;
[0064] (6) 5.0 g of polyethersulfone powder and 2.5 g of polyvinylpyrrolidone powder were added to 25.0 g of N-methylpyrrolidone, and stirred at 60° C. for 4 h to obtain a casting solution, which was then added dropwise to the wrinkled sulfonated graphene obtained in step (5), and spin-coated at a speed of 1000 rpm for 20 s. Subsequently, the wrinkled graphene was quickly immersed in anhydrous ethanol for phase inversion, and after 30 min, the obtained membrane was peeled off from the elastic glue to obtain a graphene separation membrane with a wrinkled structure.
[0065] The thickness of the sulfonated graphene / poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) layer of the prepared wrinkled graphene separation membrane is 6 μm, and the thickness of the porous polyethersulfone substrate is 72 μm.
[0066] Example 5
[0067] (1) Synthesis of graphene oxide: Weigh 1.0g natural graphite powder and 0.5g sodium nitrate and add them to 25mL concentrated sulfuric acid. Stir magnetically for 8h. Then, slowly add 3.0g potassium permanganate in an ice bath and continue stirring for 4h. Then, raise the temperature to 35°C, stir for 2h, slowly add 46mL deionized water, and then stir for 0.5h and add 140mL deionized water. Then, quickly add 10mL 30% hydrogen peroxide solution. The product is centrifuged and washed with water several times, then freeze-dried;
[0068] (2) Preparation of graphene oxide dispersion: 500 mg of graphene oxide solid was weighed and added into 1 L of deionized water, stirred for 1 h, and then ultrasonically treated in an ultrasonic cleaner for 1 h;
[0069] (3) Preparation of silver nanowire dispersion: 10 mL of commercially purchased silver nanowire with a concentration of 10 mg mL -1 Silver nanowire dispersion was diluted to 100 mL with deionized water;
[0070] (4) Place a mixed cellulose ester film with a pore size of 0.45 μm flat on a glass plate, spray the silver nanofiber dispersion prepared in step (3) onto the mixed cellulose ester film using a spray gun, dry naturally or dry at a temperature not higher than 80° C., then spray the graphene oxide dispersion prepared in step (2) onto the silver nanofiber using a spray gun, and then dry naturally or dry at a temperature not higher than 80° C.
[0071] (5) 3M VHB elastic adhesive is stretched 300% in all directions, and then the mixed cellulose ester film prepared in step (4) is tightly attached to the elastic adhesive with one side of graphene oxide, and then the mixed cellulose ester film is slowly torn off and the elastic tape is released to obtain a wrinkled graphene / silver nanowire layer.
[0072] (6) Add 5.0 g of polyacrylonitrile and 2.5 g of polyethylene glycol powder to 25.0 g of N,N-dimethylacetamide and stir at 70°C for 4 h to prepare a casting solution. The casting solution is added dropwise to the wrinkled graphene oxide prepared in step (5) and spin-coated at a speed of 1000 rpm for 20 s. Subsequently, it is quickly immersed in anhydrous ethanol for phase inversion. After 30 min, the obtained membrane is peeled off from the elastic glue to obtain a graphene separation membrane with a wrinkled structure.
[0073] The thickness of the sulfonated graphene / silver nanowire layer of the prepared wrinkled graphene separation membrane is 22 μm, and the thickness of the porous polyethersulfone substrate is 60 μm.
[0074] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a graphene separation membrane having a wrinkled structure, characterized in that: The following steps are involved: First, a nanofiber dispersion and a graphene dispersion are prepared separately, a nanofiber layer is deposited on a porous membrane substrate, and then a graphene layer is deposited on the nanofiber layer. The obtained material is then turned over and the graphene layer is tightly attached to a pre-stretched elastic tape. The porous membrane substrate is torn off, and the elastic tape is released to shrink the nanofiber layer and the graphene layer. Thereafter, a layer of organic polymer casting liquid is applied on the shrunken nanofiber layer, and the layer is immersed in anhydrous ethanol for phase inversion. Finally, the prepared membrane is peeled off from the elastic tape.
2. The preparation method according to claim 1, characterized in that: The porous membrane substrate is a polyacrylonitrile membrane, polyvinylidene fluoride membrane, mixed cellulose ester membrane, polypropylene membrane, polycarbonate membrane, polytetrafluoroethylene membrane, polyethersulfone membrane, polysulfone membrane with a flat structure, and its pore size ranges from 0.01 to 10.0 μm.
3. The preparation method according to claim 1, characterized in that: The graphene includes graphene obtained by chemical exfoliation of graphite and its derivatives, which are one or a mixture of two or more of graphene oxide, reduced graphene oxide, hydroxylated graphene, carboxylated graphene, amino graphene or sulfonated graphene; the nanofibers are carbon material nanofibers, metal nanofibers, metal oxide nanofibers, organic polymer nanofibers or inorganic nitrogen / carbide nanofibers.
4. The preparation method according to claim 3, characterized in that: The carbon material nanofibers are carbon nanotubes or carbon nanofibers or a mixture of one or two thereof; the metal nanofibers are gold nanofibers, silver nanofibers, copper nanofibers, cobalt nanofibers, iron nanofibers, and nickel nanofibers or a mixture of one or more thereof; the metal oxide nanofibers are iron oxide nanofibers, zinc oxide nanofibers, titanium oxide nanofibers, aluminum oxide nanofibers, gallium oxide nanofibers, and tin oxide nanofibers or a mixture of one or more thereof; the organic polymer nanofibers are poly(p-phenylene terephthalamide) nanofibers or poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) nanofibers or a mixture of one or two thereof; the inorganic nitrogen / carbide nanofibers are silicon carbide nanofibers and boron nitride nanofibers or a mixture of one or two thereof.
5. The preparation method according to claim 1, characterized in that: The deposition method is one of vacuum filtration, spraying and evaporation self-assembly; the elastic tape is pre-stretched to 150% to 400% of the original length.
6. The preparation method according to claim 1, characterized in that: The organic polymer casting solution is a viscous solution obtained by uniformly stirring a high molecular organic polymer, a pore-forming agent and an organic solvent at 40-80°C.
7. The preparation method according to claim 6, characterized in that: The high molecular polymer is a mixture of one or more of polyacrylonitrile, polyvinylidene fluoride, polyether sulfone, and polysulfone; the pore-forming agent is a mixture of one or more of polyvinyl pyrrolidone and polyethylene glycol; the organic solvent is a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and the mass ratio of the high molecular polymer, the pore-forming agent, and the organic solvent is 1:(0.2-1):5-10.
8. A graphene separation membrane with a wrinkled structure obtained by the preparation method according to any one of claims 1 to 7.
9. The graphene separation membrane with a wrinkled structure according to claim 8, characterized in that: The graphene separation membrane has a layered structure, including a porous organic polymer base layer, a nanofiber middle layer and a wrinkled graphene surface layer; the thickness of the porous organic polymer base layer is 20-200 μm, the thickness of the nanofiber middle layer is 1-50 μm, and the thickness of the wrinkled graphene surface layer is 1-50 μm.
10. Use of the graphene separation membrane with a wrinkled structure according to claim 8 or 9 in wastewater treatment.
Citation Information
Patent Citations
Preparation method of extensive inorganic flexible LED array
CN105006450A
Multilayer composite thermal conductive film and preparation method thereof
CN108129685A
Graphene / polymer nanofiber composite membrane, preparation method therefor and application of graphene / polymer nanofiber composite membrane
CN111150367A
Wrinkled graphene oxide / nanofiber composite membrane and preparation method and application thereof
CN111214962A
Flexible extensible mechanical sensing system based on self-energization and preparation method
CN112097967A